Discoloration of gingiva in the presence of fixed dental restorations - Ristić Ljubiša; Miljković Živorad; Ilić Srbislav; Đurić Tatjana (Vojnosanitetski Pregled)
Aim. To investigate the frequency of discoloration of gingiva in the presence of fixed dental restorations, regarding the type of alloy of which restorations were made, and to show histopathological changes of discolored gingiva. Methods. One hundred and eighty four patients of both sexes were examined. The average age of the examinees was 52. They were divided into four groups according to the alloys from which their restorations were made. Standardized history questionnaires and clinical examination procedures were developed for this study. In ten examinees, whose teeth were indicated for extraction and who had a discoloration of gingiva, the samples of tissue were taken from the discolored gingiva for histopathological examination. Results. Our results showed the presence of discolored gingiva in all four groups. It was most frequent in the examinees with fixed restorations made of Ni-Cr alloy (43,5%) and less frequent in those with fixed dental restorations made of gold alloy (26,5%). Histopathological examination showed the presence of tissue foreign body granulomas with giant cells in which the metal particles were found, partially as small and partially as large particles. Conclusion. Results suggested that grayish discoloration of gingiva was present in all four groups of examinees. The highest number of examinees with discolored gingiva was in the group with restorations made of Ni-Cr alloy. Grayish discoloration of gingiva was a consequence of incorporation of metal particles into gingival tissue.